Subjective and objective stress during body exposure: a comparison of adolescents with anorexia nervosa versus high body dissatisfaction - Valeska Stonawski; Louisa Kuper; Nicolas Rohleder; Gunther H. Moll; Hannah Fischer; Anne-Christine Plank; Tanja Legenbauer; Oliver Kratz; Stefanie Horndasch (Frontiers in Psychiatry)
ObjectiveBody dissatisfaction (BD) is a risk factor for the development of an eating disorder (ED) and a negative predictor for treatment outcome in adolescents with anorexia nervosa (AN). As a clinical core symptom and a relevant maintaining factor of AN, body image disturbance and BD are highly relevant target variables for therapeutic interventions. Body exposure (BE) was found as being effective for reducing BD in adolescents with EDs and high BD. However, the underlying mechanisms of BE are still not clear, with habituation processes being discussed as one possible mechanism.MethodsAffective and neurobiological processes during a four-session computer-based BE intervention were investigated. Within a controlled design comparing adolescents with AN (n = 34) vs. adolescent patients with high BD (n = 17) but without a diagnosed ED, subjective (stress ratings; 11-point Likert scale) and objective (salivary cortisol and alpha-amylase [sAA]) stress measures were assessed at four time points at each exposure session (start, +10 min, +30 min/end, +60 min/recovery). ED and depressive psychopathology were assessed via self-rating questionnaires.ResultsA between-session habituation effect was found for subjective stress ratings and sAA levels with decreasing scores throughout the four sessions. A within-session habituation was found for cortisol levels. Higher psychopathology was associated with subjective stress ratings. There were no group differences between AN and BD regarding ED psychopathology or subjective or objective stress measures. Subjective and objective stress measures were mainly not associated with each other.ConclusionsHabituation processes were found for subjective and objective stress, which might enhance motivation to continue BE interventions and thus increase their impact. BD seems to be a transdiagnostic phenomenon with BE as a successful intervention independent of psychiatric diagnosis. Current findings should be validated in larger samples, and the hypothesis of a transdiagnostic BD should be investigated in future research.